REALISASI KERJASAMA JOINT WORKING GROUP ANTARAINDONESIA DAN INGGRIS DI BIDANG PENDIDIKAN TINGGIPERIODE 2018-2021 - Raissa Cindy Laksitadewi (2022)
The emergence of the era of globalization has putted demands in quality of higher education for every country. To be able to compete globally, a country get to improve the quality of higher education, including Indonesia. Government intervention is very important in determining the direction of the development of higher education in Indonesia. The government in improving the quality of higher education need to be able to create good and beneficial policies for the citizens. This study used a qualitative approach by conceiving the datas obtained from the parties involved in this case and analyzing them objectively with the concept of national interest and the concept of political education. The result of this study is that the realization of the programs of the Joint Working Group cooperation between Indonesia and The UK had almost entirely been implemented, although there were obstacles. However, the government had taken other steps that could facilitate the continuity of the cooperation which gave some positive impacts on Indonesia. Thus, it can be told that the overall realization of the joint Working Group cooperation between Indonesia and The UK in the field of higher education for the 2018-2021 period had been implemented well. Keywords: Cooperation, Higher Education, Indonesia, The UK, Joint Working Group